Long-term in vivo expression of the human glucocerebrosidase gene in nonhuman primates after CD34+ hematopoietic cell transduction with cell-free retroviral vector preparations. - Xu, L C (1995)
Successful gene transfer into stem cells would provide a potentially useful therapeutic modality for treatment of inherited and acquired disorders affecting hematopoietic tissues. Coculture of primate bone marrow cells with retroviral producer cells, autologous stroma, or an engineered stromal cell line expressing human stem cell factor has resulted in a low efficiency of gene transfer as reflected by the presence of 0.1-5% of genetically modified cells in the blood of reconstituted animals. Our experiments in a nonhuman primate model were designed to explore various transduction protocols that did not involve coculture in an effort to define clinically useful conditions and to enhance transduction efficiency of repopulating cells. We report the presence of genetically modified cells at levels ranging from 0.1% (granulocytes) to 14% (B lymphocytes) more than 1 year following reconstitution of myeloablated animals with CD34+ immunoselected cells transduced in suspension culture with cytokines for 4 days with a retrovirus containing the glucocerebrosidase gene. A period of prestimulation for 7 days in the presence of autologous stroma separated from the CD34+ cells by a porous membrane did not appear to enhance transduction efficiency. Infusion of transduced CD34+ cells into animals without myeloablation resulted in only transient appearance of genetically modified cells in peripheral blood. Our results document that retroviral transduction of primate repopulating cells can be achieved without coculture with stroma or producer cells and that the proportion of genetically modified cells may be highest in the B-lymphoid lineage under the given transduction conditions.